Cerâmica Marajoara: caminho para compreender a pré-história da Amazônia - Amorin, Lilian Bayma (2005)
Marajoara Ceramics: a path to understanding Pré-History in Amazonia' underlines the importance of disseminating science produced in research institutions. It does so through the study of the archaelogical Marajoara Collection under the responsibility of the Goeldi Museum. I attempt to demonstrate how scientific knowledge raises awareness and promotes recognition of the material culture of peoples already extinct, who even though did not know writing as we do, established a code of communication and social rules yet to be fully understood. The work aims at estimulating interest on the preservation of cultural heritage as means to realize how it may or may not had impact on society at present. Finally, I produced a catalogue 'Marajoara Ceramics: the communication of silence' which stresses the need to show items of the collection under study as means to share scientific knowledge with the whole of society.